Prevalence of dysmenorrhea and predictors of its pain intensity among Palestinian female university students - Heba A. Abu Helwa; Areen A. Mitaeb; Suha Al-Hamshri; Waleed M. Sweileh (BMC, 2018)
Abstract Background Few studies on gynaecological problems of young females in Arab countries were published. The aim of this study was to determine the prevalence of dysmenorrhea and predictors of its pain among university students in Palestine. Methods A cross - sectional study was carried out on a randomly selected sample of An-Najah National University female students. A pre-designed questionnaire, which included questions regarding menstrual cycle, pain during menstruation, life style, nutritional habits, and symptoms associated with menstrual pain, was used. Pain intensity was measured using visual analogue scale. Results A total of 956 female students were involved in the study. Of the total study sample, 846 (85.1%) reported having pain during menstruation; i.e. dysmenorrhea. Dysmenorrhea was significantly [(p = 0.027); OR = 1.5, 95% CI (1.05-2.19)] associated with age at menarche. The mean score of pain among dysmenorrhic females was 6.79 ± 2.64. The majority (654; 80.34%) of dysmenorrhic females reported having moderate/ severe pain. Univariate analysis using Chi-square test for factors associated with moderate/severe pain among dysmenorrhic females were irregular cycle [(p = 0.015); OR = 1.57, 95% CI = (1.09-2.30)], skipping breakfast [(p < 0.001); OR = 1.93, 95% CI = (1.33-2.79)], academic specialization [(p = 0.03; OR = 2.2, 95% CI = (1.21-3.98)] for medical specialization with reference to students in humanities), high stress level [(p = 0.036; OR = 1.53, 95% CI = (1.03-2.28)], and living in dormitories [(p = 0.034); OR = 1.72, 95% CI = (1.04-2.86)]. Multivariate analysis using binary logistic regression enter method showed that medical specialization [(p = 0.045); OR = 1.92, 95% CI = (1.02-3.64)] for medical students with reference to students in humanities), skipping breakfast [(p = 0.001); OR = 1.96, 95% CI = (1.35-2.86)], and irregular cycle [(p = 0.022); OR = 1.56, 95% CI = (1.07-2.29)] were the only significant predictors of moderate/severe dysmenorrhic pain. Conclusion There is a high proportion of dysmenorrhea among Palestinian female university students. Skipping breakfast was the strongest predictor for moderate/severe dysmenorrhea. Increased awareness regarding factors that might influence the intensity of dysmenorrhic pain is needed.